Population pharmacokinetics of letermovir following oral and intravenous administration in healthy participants and allogeneic hematopoietic cell transplantation recipients. (12th March 2021) - Prohn, Marita; Viberg, Anders; Zhang, Da; Dykstra, Kevin; Davis, Casey; Macha, Sreeraj; Sabato, Philip; de Alwis, Dinesh; Iwamoto, Marian; Fancourt, Craig; Cho, Carolyn R.
Abstract: Letermovir is indicated for prophylaxis of cytomegalovirus infection and disease in allogeneic hematopoietic stem cell transplant (HSCT) recipients. Two‐stage population pharmacokinetic (PK) modeling of letermovir was conducted to support dose rationale and evaluate the impact of intrinsic/extrinsic factors. Data from healthy phase I study participants over a wide dose range were modeled to evaluate the effects of selected intrinsic factors, including pharmacogenomics; next, phase III HSCT‐recipient data at steady‐state following clinical doses were modeled. The model in HSCT recipients adequately described letermovir PK following both oral or i.v. administration, and was consistent with the healthy participant model at steady‐state clinical doses. Intrinsic factor effects were not clinically meaningful. These staged analyses indicate that letermovir PK in HSCT recipients and healthy participants differ only with respect to bioavailability and absorption rate. The HSCT recipient model was suitable for predicting exposure for exposure–response analysis supporting final dose selection.